Study on water quality of the Tasik Titiwangsa, Kuala Lumpur - Nur Izzati, Mat Zin (2014)
The purposes of the study was to determine the current water quality status of the Tasik Titiwangsa (Titiwangsa Lake) and to obtain the water quality classified based on Interim National Water Quality Standard (1NWQS) for Malaysia and Water Quality Index (WQI) of the selected sampling station. A total of six sampling station were selected for this study which were named as station 1, 2, 3, 4, 5 and 6. Sixteen water quality parameters were analyzed based on in-situ and ex-situ analysis at the sample were collected on September, October and November. Laboratory analysis was carried out according to the standard method. In-situ water quality parameters were such as pH, dissolve oxygen, electrical conductivity, turbidity, temperature and TDS. For ex-situ water quality parameters included TSS, animoniacal nitrogen, COD, BOD, nitrate, phosphate, sulphate, total coliform, E-coli and oil and grease. The result showed that the water quality of the Tasik Titiwangsa was classified as Class III based on WQI which suitable for recreational activities and body contact. However, the activities such as wedding ceremony, water sports and equestrian sports venue have taken place in surrounding of the lake consequently affected the water body of Tasik Titiwangsa and it might be cause of the lake pollution and some further action must be considered for the best in future.